N035 The use of intravenous (IV) ferric carboxymaltose in a paediatric IBD population. (16th January 2018) - Crook, K; Tyrrell, T; Hyer, W
Abstract: Background: Anaemia in children with IBD has a reported prevalence as high as 70%. In line with the BSPGHaN Iron deficiency in Paediatric IBD guideline (2015) the use of IV iron within our population to manage anaemia has increased. The only IV iron preparation available on the hospital formulary is Ferinject (Ferric carboxymaltose) however this posed problem's as many of our patients are below the licensed age. Therefore the purpose of this audit was to evaluate the safety and efficacy of Ferinject within our paediatric population. Methods: Between February 2014 and July 2017, 29 children with IBD have received an Iron infusion on the Paediatric Daycare unit at Northwick Park/St Mark's Hospital, of these 14 were under the licensed age of 14 years. The main reasons for receiving an IV iron infusion was low Hb and associated symptoms of lethargy, prior intolerance of oral iron supplements and non-response to oral iron. Infusions were given over 15–30 min with 30 min post infusion observation. Patients 25–35 kg were given 500 mg in a single dose, below 25 kg the dose was calculated to 20 mg/kg as per maximum administration in a single IV dose guidelines. Results: Of the 29 patients identified 23 were diagnosed with Ulcerative colitis. The average age at infusion was 12 years (range 4 years 2 months to 17 years 7 months). Post infusion bloods were taken between 6 and 10 weeks after the last infusion. Only 7 of 29 patients did not recover their Hb to within normal range for age and all were within 10 g/l of the normal range. There were no reported infusion reactions and no patients required a blood transfusion. Lethargy improved following the first infusion for patients who exhibited this symptom. Conclusions: Despite the small numbers, our audit indicates that IV Iron in the form of Ferinject is safe and effective in children as young as 4. The use of IV iron in children with IBD has reduced the need for blood transfusion's and oral iron supplements.